PENETAPAN KADAR FLAVONOID TOTAL EKSTRAK ETANOL KULIT BUAH ALPUKAT (Persea americana Mill.) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Aminah Aminah; Nurhayati Tomayahu; Zainal Abidin (Jurnal Fitofarmaka Indonesia, 2017)
Avocado plant (Persea americana Mill.), belongs to Lauraceae family which have medicinal properties. Avocado peel contains flavonoid compounds that can be used to protect and reduce the skin damage against UV rays. This study aimed to determine the total flavonoids content of the ethanol extract of the avocado peel using UV-Vis spectrophotometry. The ethanol extract of avocado peel was obtained by maceration with ethanol. The qualitative analysis used FeCl3 by forming green complex. The determination of total flavonoids content is conducted based on AlCl3 method with total flavonoids expressed in QE (Quercetin equivalent) at the maximum wavelength of 435 nm. The result showed that the average content of flavonoid total is 4.0122 mgQE/g extract.